Deformation of shuttlecock skirt - Tan, De Qing (Nanyang Technological University, 2022)
Many people across the world play badminton, either recreationally or competitively. There are two kinds of shuttlecocks on the market today: feathered shuttlecocks and synthetic shuttlecocks. However, feathered shuttlecocks are favoured in competition due to their constant performance. The Badminton World Federation (BWF) rates feathered shuttlecocks based on three criteria: aerodynamics, durability, and stability. As technology advances, the existing method of assessing shuttlecock performance can be enhanced further, and new testing criteria can be established. The objective of this Final Year Project (FYP) is to investigate the badminton shuttlecocks’ durability and track the feathers’ deformations. This experimental investigation builds on the previous FYPs where Aeroplane EG1130, Yonex AS50, [1] and three random shuttlecocks were tested. [2] In this experiment, four BWF-approved shuttlecocks, two non-BWF-approved shuttlecocks, and two chemically modified shuttlecocks were subjected to a modified durability test. The shuttlecocks are Lining A+300, Aeroplane EG1130, RSL Tourney Classic, Yonex AS50, Victor Gold 1, Ashaway Official, Chemical-Treated A, and Chemical-Treated B, respectively. The BWF examines shuttlecock durability by picking three shuttlecocks at random and having professional players smash each shuttlecock for 10 stokes. This procedure is being recorded, and any deformations will be checked after these 10 strokes. The shuttlecocks were evaluated in a specifically built test platform that reliably imitated the smashing action of a racket, which distinguished the modified durability test from the BWF durability test. Every shuttlecock used in this experiment will be exposed to a series of 90 hits at a greater velocity of 35.34 m/s than the previous testing at a velocity of 20 m/s. The shuttlecock deformations are documented at the first sign of deformation and thereafter at every interval of 10 strikes. Photographs of the feather's deformations will be displayed. The results demonstrate that Lining A+300, Aeroplane EG1130, Yonex AS50, RSL Tourney Classic, and Victor Gold 1, have more deformations than Ashaway Official and the two chemically modified shuttlecocks. Except for Ashaway Official, the data shows that chemically treated shuttlecocks are typically more durable than other shuttlecocks. Because these early tests were conducted on a single sample size, it is suggested to perform further testing on these eight shuttlecocks on a larger scale to better determine the durability of these shuttlecocks. It is also suggested to increase the velocity of the racquet used to propel the shuttlecock to a velocity closer to the BWF's clear test speeds in the future testing.